EKSPLORASI POTENSI SITUS-SITUS PARIWISATA DI GUNUNGSARI: SEBUAH KAJIAN AWAL RISET AKSI PARTISIPATIF TENTANG PARIWISATA BERBASIS MASYARAKAT - Hipolitus K. Kewuel; Irsyad Martias; Aji Prasetya W.U; Manggala Ismanto; Siti Zurinani; Ari Budiyanto; Edlin Dahniar; Dyah Rahayuningtyas (Journal of Tourism Destination and Attraction, 2020)
The aim of this preliminary participatory action research (PAR) is to explore potential tourism sites in Gunungsari Village, Batu City, East Java. As a PAR, it implements the ecotourism concept, which is called community-based tourism (CBT) by projecting the participatory mapping (PM). As a result, this PM activity reveals the diversification of potential tourism sites which can be classified into five categories: (1) religious and cultural tourism (RCT), (2) special interest tourism (SIT), (3) agro-tourism (AT), (4) home industry tourism (HIT), and (5) educational tourism (ET). Moreover, this diversification can give significant contributions in developing tourism planning programs based on the CBT perspective aiming to empower local communities.